Print media as a migrant advocacy tool: A case of Indonesian language print media in Hong Kong - Irfan Wahyudi; Panizza Allmark (Masyarakat, Kebudayaan dan Politik, 2018)
Hong Kong is listed as one of the most popular countries for Indonesian migrant workers. In 2012, more than 160,000 Indonesian migrant domestic workers (IMDWs) live in Hong Kong, and more than 90% of them are women. Hong Kong is the premium destination for IMDWs because of its moderately higher salaries, good laws and regulations, and its ambience of independence. The IMDWs can also access multiple media platforms, ranging from print media to the Internet. This writing specifically discuss about Indonesian newspaper published in Hong Kong and its relation with migrant activism. The research found that there are four existing Indonesian language newspapers in Hong Kong: Suara, Apa Kabar Plus, Koran Indonesia (KINDO), and Berita Indonesia. Conflicts between newspaper journalists and migrant organizations have affected the newspapers’ credibility. The methodology used is ethnography. Fieldwork conducted in Hong Kong Special Administrative Region (SAR) in 2013, 2014 and 2018. Participant observations, in depth interviews, and focus group discussions were conducted in this research.